Parallelization of the compact methods for the Navier-Stokes equations - Rokicki, Jacek; Floryan, Jerzy M. (Computer Assisted Methods in Engineering and Science, 2023)
The proposed algorithm is based on the fourth-order compact discretization schemes for the Navier-Stokes equations in streamfunction-vorticity-pressure formulation. The equations are expressed in terms of a general orthogonal curvilinear coordinate system which allows for modelling non-standard geometries. Two distinct parallelization strategies are considered. The first one relies on the domain decomposition approach, in which each sub domain is served by a different processor. In the second strategy, suitable for massively parallel computers, each processor serves a single grid point . The comparison of the performance of various computing platforms is presented, including a 2048-processor MasPar computer.